A Decision Support System Based on a Genetic Algorithm for the Utilization of Leftovers. Issue 3 (3rd May 2016) - Fu, Hsin-Pin; Ku, Cheng-Yuan; Chang, Tsung-Sheng
Abstract: There are usually some leftovers (usable pieces of raw material) and scraps (unusable pieces of raw material).generated after the completion of a manufacturing process. These leftovers consist of many different types, materials, styles and sizes so the use of such materials is difficult to manage, resulting in a significant material management problem for manufacturers. This study examines ways to use these leftovers and proposes the application of a genetic algorithm to handle the problem of matching usable leftovers to incoming orders. In order to verify the feasibility of the solution, a decision support system was implemented, based on a genetic algorithm. With lots of experimental results, we conclude this method is thus of considerable value to the managers of manufacturing factories.